Studies on the Occurrence and Population Distribution of Nematodes with yam (Dioscorea rotundata Poir) tubers in Benue State, Nigeria - Habib, S. Solomon, V. Isegbe, M. A. (Journal of Ecobiotechnology, 2017)
Yam (Dioscorea spp) nematodes have been variously reported to reduce tuber yield and quality worldwide. In the present study, a survey was done to estimate types, frequency and population density of nematodes associated with yam tubers at each of the Local Government haedquarters and two villages in Benue state of Nigeria. A total of 250 yam tubers were sampled randomly in the survey markets between April and May, 2017. Each yam sample was processed by peeling the periderm (one inch thick) out of which a 10 g sub-sample tuber was separately put in a blender with some quantity of water and mercerated at low speed for 15 seconds. Plant-parasitic nematodes were recovered from the yam tubers using a modified extraction tray method. Five nematode species were found in association with yam tubers as follows: Scutellonema bradys, Meloidogyne spp, Pratylenchus spp, Rotylenchulus spp and Tylenchus spp. Scutellonema bradys was the most ubiquitous, occuring at a 100% frequency rating in all the samples while Meloidogyne spp, Pratylenchus spp, Rotylenchulus spp and Tylenchus spp. were 29.60%, 16.80%, 8.80% and 4.80% respectively. Though the study revealed that Rotylenchulus spp and Tylenchus spp. were poor parasites of yam tubers, yet there was a widespread distribution of Scutellonema bradys, Meloidogyne spp and Pratylenchus spp on yam tubers in Benue State of Nigeria, thus control of plant-parasitic nematodes is encouraged for improved tuber quality.